Becoming Literate Digitally in a Digitally Literate Environment of Their Own. Issue 5 (March 2017) - Ian O'Byrne, W.; Pytash, Kristine E.
Abstract: This commentary begins with a summary of the current landscape of literacy, technology, and education. The authors then examine A Domain of One's Own as an important new initiative and explore how teachers and schools can implement this initiative. The authors contend that the building and developing of A Domain of One's Own is a good example of how schools can engage students in complex and meaningful literacy practices. In addition, the authors discuss the challenges and opportunities of providing students with a domain of their own to use as they start their literacy careers in our schools.